Ferramenta computacional para auxiliar na redução de custos com energia elétrica - Ruviaro, Adrieli (2019)
Finding alternatives to reduce electricity costs is important, even more so if they are available on a single platform, and can be analyzed separately or together, quickly and practically, indicating accurate results. This is because, besides the demand and the cost of energy have a tendency to grow, it represents a significant portion in the general expenses of the consuming units. There are several possibilities that can result in a reduction in the expenses involved with electricity, but as most of them involve financial investment, it is essential that there is an economic justification. As is the case with energy efficiency actions and the installation of sources of electricity generation. The contractual revision with the concessionaire, in turn, can result in financial savings without involving investment, which together with the previous options, can help in the feasibility in a shorter period of time. Moreover, as these actions impact each other, it is essential that they be organized in an intelligent order, thus contributing to each other. Research did not identify a software or methodology comprehensive to all consumer profiles connected to the network, contemplating different studies according to the opportunities to reduce electricity costs, taking into account their feasibility. Therefore, the objective of this dissertation is to develop a computational tool, taking these considerations into account, thus assisting consumers in their decision making, in view of the possibilities to reduce electricity costs, taking into account the viability exposed through cumulative cash flow and payback. For this, the methodology created was separated into five steps: in the first one the input data is specified; in the second, the demand and modality contract is revised; in the third, energy efficiency methods, such as lighting, motors and capacitor bank installation, to correct the power factor; in the fourth, the installation of electric power generation systems from photovoltaic modules and diesel generator sets is analyzed, as well as the contractual revision, and; on the fifth, the final report is presented, in accordance with all approved analyzes. At first, this method was developed in Microsoft Excel, but it can be applied on several other platforms, for different audiences, depending on the formatting and the template used. The tool itself displays most of the results graphically and has an easy-to-understand and easy-to-handle layout with over 160 interconnected tabs. To show the functionality and possibilities it offers, three case studies are conducted, with consumers of different profiles and needs. The results show that, depending on the consumer profile, a large economy can be obtained, or that it is not worth making changes to existing facilities or hiring both the modality and the demand. Therefore, as there is no standard, it further justifies the importance of using the tool developed here.